KOMUNIKASI ANTAR ANGGOTA KELUARGA DI TENGAH PERKEMBANGAN MEDIA KOMUNIKASI TELEPON PINTAR - Suci Sofralsa; Atika Latifa Ulfat (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2022)
One way of communicating that is currently very developed is by using the media. The development of advances in communication technology has led to the use of social media via smart phones (cellphones) to spread to all levels of human age and also to relationships between family members. Where individuals who are far away can be near and vice versa who are near become far away even as if no one is beside or near him. Father, mother and children when they are inside the house after activities outside the house, look like they are doing direct communication activities. But in reality, they are all still busy on social media by using their own communication media (cellphone or laptop). This research uses a mixed research technique of Mixed Method Research (MMR), namely, by combining qualitative and quantitative research types. The development of communication media technology has an impact on interactions among humans. There were changes in the way of communicating, the atmosphere of communication, the quality and quantity of this communication. This also affects the communication that exists and is built between family members